2020
DOI: 10.12928/telkomnika.v18i2.14906
|View full text |Cite
|
Sign up to set email alerts
|

Fisher-Yates and fuzzy Sugeno in game for children with special needs

Abstract: As a country that has its language, English is an international language that needs to be mastered. Until now, the mastery of English in Indonesian on an international scale is in a low category. Learning English should be taught to children from an early age. For children with special needs, special learning methods are needed so that the material is conveyed. Educational games can be used as an interesting learning media. In this study, an English educational game was created that had the concepts of a quiz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…The technological innovations in learning for people with special needs included the so-called "e-educational game strategies" based on platforms Electronic and electronic application stores. Studies by Zilz and Pang (2021), Anber and Jameel (2020), Ramdania (2020), Gandolfi (2018), Abdallah and Fayyoumi (2016), Berns et al (2016), , and Durkin et al (2015) have revealed the effectiveness of activating the uses of educational technology, including the platforms and applications of electronic educational games to develop the perceptions of the Arab child, especially those with special needs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The technological innovations in learning for people with special needs included the so-called "e-educational game strategies" based on platforms Electronic and electronic application stores. Studies by Zilz and Pang (2021), Anber and Jameel (2020), Ramdania (2020), Gandolfi (2018), Abdallah and Fayyoumi (2016), Berns et al (2016), , and Durkin et al (2015) have revealed the effectiveness of activating the uses of educational technology, including the platforms and applications of electronic educational games to develop the perceptions of the Arab child, especially those with special needs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Recently, Zafar et al (2021) found that the "Avatar Approach" has a significant role in providing an electronic platform for teaching English language vocabulary, sentences, and phrases to special needs deaf students. It is worth involving media and technology to support special needs students learning process to facilitate the learning English language (Ramdania et al, 2020, Gandolfi et al, 2018, Durkin et al, 2015. Educational and instructional electronic games can support special needs students' language progress Ramdania, et al (2020) used Fisher-Yates and Fuzzy Sugeno games to measure special needs students' level of understanding of English materials progress.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Algoritma Fisher-Yates memiliki beberapa tahapan dalam proses pengacakan. Berikut adalah tahapan-tahapan dari proses pengacakan sebagai berikut [16,17]: Tabel 1 menjelaskan alur dari proses pengacakan algoritma Fisher-Yates yang diantaranya: 1) Menentukan jumlah data yang ada.…”
Section: Algoritma Fisher-yates Shuffleunclassified
“…In learning, games are usually applied to evaluate students' understanding of the material they have learned. The evaluation model often collects questions in a quiz, puzzle, questionnaire, etcetera [2,3]. In a game, gamification plays a vital role in increasing motivation [4].…”
Section: Introductionmentioning
confidence: 99%